Relationship between body mass index and dental caries in children, and the influence of socio‐economic status. (17th October 2016) - Kumar, Santhosh; Kroon, Jeroen; Lalloo, Ratilal; Kulkarni, Suhas; Johnson, Newell W.
Abstract : Objectives: To determine the association of body mass index (BMI) with dental caries in Indian schoolchildren, and to analyse the influence of socio‐economic status (SES). Methods: The study population consisted of 11‐ to 14‐year‐old children from Medak District in Telangana State, India. The Indian Academy of Paediatrics 2015 growth charts were used to categorise children as underweight, overweight, normal or obese, based on their BMI. Data on the SES of the family were collected through questionnaires. Clinical examination for dental caries was performed by a single examiner. Results: A total of 1, 092 subjects returned questionnaires and were clinically examined (giving a response rate of 85%). There were no significant differences in caries prevalence and experience across the categories of BMI. However, caries prevalence and experience in overweight children were 24.8% and 0.69 ± 1.51, respectively, while the corresponding values in normal‐weight children were 35% and 0.85 ± 1.50, respectively. Among children of high‐SES families, overweight children had approximately 71% fewer caries than did those who were normal weight [incidence rate ratio (IRR) = 0.29; 95% CI: 0.11–0.78)]. Conclusions: BMI was not associated with dental caries prevalence and experience in this population. The association of BMI with dental caries varied across SES categories. In the high‐SES category, overweight children experienced fewer caries than did normal‐weight children.